Observer’s congruent response when boss put their colleague’s down, A moderated mediation mechanism - Rasheed, Maria; Anwar, Dr. Farooq; Ali, Tayyab; Hameed, Ahmed Abdul (The journal of contemporary issues in business and government, 2021)
Prior research mostly covers the instigator and target perspective of workplace incivility and overlooked the third parties’ reaction. The current research aims to examine the congruent social emotion of the observer after witnessing the incivility toward coworkers with the lens of affective event theory. It also examines the behavioral response of the observer due to that social emotion. Through the time-lagged survey conducted in the service industry, the results showed that vicarious workplace incivility was positively associated with empathy towards a coworker, that emotion is further positively associated with helping behavior towards victims. This relationship is moderated by gender, such that females are more sensitive towards incivility. Third parties experience positive social emotions of empathy and try to buffer the situation through helping behavior. Our findings try to examine the interpersonal, target-directed outcomes of vicarious workplace incivility. The results of the study contribute to both theory and practice.